EFFECTS OF DIPOLE MODE AND EL-NINO EVENTS ON CATCHES OF YELLOWFIN TUNA (Thunnus albacares) IN THE EASTERN INDIAN OCEAN OFF WEST JAVA - Khairul Amri; Ali Suman; Hari Eko Irianto; Wudianto Wudianto (Indonesian Fisheries Research Journal, 2015)
The effects of Indian Ocean Dipole Mode and El Niño–Southern Oscillation events on catches of YellowfinTuna (Thunnus albacares) in the Eastern Indian Ocean (EIO) off Java were evaluated through the use of remotely sensed environmental data (sea surface temperature/SST and chlorophyll-a concentration/SSC) and Yellowfin Tuna catch data. Analyses were conducted for the period of 2003–2012, which included the strong positive dipole mode event in association with weak El-Nino 2006.Yellowfin Tuna catch data were taken from Palabuhanratu landing place and remotely sensed environmental data were taken from MODIS-Aqua sensor.The result showed that regional climate anomaly Indian Ocean Dipole Mode influenced Yellowfin Tuna catch and its composition. The catches per unit effort (CPUE) of Thunnus alabacares in the strong positive dipole mode event in 2006 and weak El-Nino events in 2011 and 2012 was higher. The increase patern of CPUE followed the upwelling process, started from May-June achieved the peak between September-October.Very high increase in CPUE when strong positive dipole mode event (2006) and a weak El-Nino events (2011 and 2012) had a relation with the increase in the distribution of chlorophyll-a indicating an increase in the abundance of phytoplankton (primary productivity) due to upwelling. In contrast, yellowfin tuna CPUE is very low at the La-Nina event (2005), though as the dominant catch when compared to others.